Helicobacter pylori infection combined with non-alcoholic fatty liver disease increase the risk of atherosclerosis: Focus in carotid artery plaque - Yu, Lo-Yip (Medicine (Baltimore), 2019)
Atherosclerosis has severe consequences on human health. Carotid artery plaques are a condition typically caused by atherosclerosis. Previous studies showed that nonalcoholic fatty liver disease (NAFLD) and Helicobacter pylori (H pylori) are risks factors for carotid artery plaque formation. We hypothesize that the combination of NAFLD with H pylori infection increases the risk of carotid artery plaque formation. A total of 4669 subjects aged > 40 years who underwent routine health checkups between January 2006 and December 2015 were retrospectively reviewed. A serial examination, including abdominal ultrasound, carotid artery ultrasound and esophago-gastroduodenoscopy (EGD), and biopsy urease testing, was conducted. In total, 2402 subjects were enrolled. There were no differences in H pylori infection status among patients with or without NAFLD. There was a trend of more participants with both NAFLD and H pylori infection (number [N]=583) presenting carotid artery plaque (N = 187,32.08%) than participants without NAFLD and H pylori infection (N = 589) who presented plaque formation (N = 106, 18.00%). Participants who had both H pylori infection and NAFLD had the highest risk of any carotid artery plaque (odds ratio [OR], 1.93; 95% confidence interval [CI], 1.413–2.636) based on a multivariate logistic regression analysis. This analysis also showed that age >60 years, male sex, low-density lipoprotein (LDL) >130 mg/dL, and H pylori infection were independent risk factors for concomitant NAFLD and carotid artery plaque formation. The combination of H pylori infection and NAFLD increases carotid artery plaque formation. H pylori eradication and NAFLD control may be warranted to prevent carotid artery plaque formation.